PENANGGULANGAN KEMISKINAN PADA PETANI BERLAHAN SEMPIT DI AGROEKOSISTEM LAHAN KERING DATARAN TINGGI BERBASIS SAYURAN - ZAKARIA, AMAR K. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
Poverty Alleviation for Small Scale Farmers in Horticulture Based Upland. The strategy of Agricultural development is directed to improve the income of farmers and rural society, especially small scale farmers. This study was conducted in upland area of Agam District, West Sumatera. The dominant crops cultivated in this area were horticulture, mainly vegetables. The results of the study showed that agricultural sector contributed about 89.2 percent of household income for the good access area and about 67.8 percent for the poor access area. Based on the status and stability of income, the results showed that the medium income level had a high stability.
Keywords: Income, Farming, Horticulture, Small Scale Farmers